Foreign Policy as Part of Strengthening the Polish Economy in the World: the Ethical Aspect - Pawlak, Mateusz (Annales. Etyka w Życiu Gospodarczym, 2014)
The technological, economic and political advances of the 20th and 21st centurieshave established new conditions for the development of civilization. The worldeconomy has simultaneously expanded (the number of states/organization participatingin world trade or the volume of heterogeneous transactions) and shrunk(close interrelations between transactions, no matter their geographic origins).Economic policy has gained an indispensable role in the creation of order in internationalrelations and foreign policy. The tendency to prioritize foreign policyaims towards economic policy aims has resulted in ‘reverse flow’, i.e. foreignpolicy has become a central part of national economic policy.The engagement of external action services and public budget in economicpromotion and investments triggers (inter alia) the ethics dilemma. The mentionedethical aspect is often omitted when discussing ‘the economic foreign policy’. Forinstance, the ethics dilemma can appear when development and humanitarian aidare taken into account or when it comes to assessing the results (and membership)of economic missions. In this context, the author analyses the Polish foreign policyexample and attempts to answer two questions. First, are the economic activitiesperformed by external action services effective? Second, are the mentionedactivities in accordance with the social ethical code of conduct? The author focuseson three elements – development and humanitarian aid, the participation ofPolish diplomats in economic promotion, and economic missions.